Screening of Mercury pollution sources to European inland waters using high resolution earth surface data - Pistocchi, Alberto; Cinnirella, Sergio; Mouratidis, Pavlos; Rosenstock, Nele; Whalley, Caroline; Sponar, Michel; Pirrone, Nicola (Frontiers in Environmental Science, 2022)
Mercury pollution is a cause of high concern for European freshwaters. In this study, we use modelled atmospheric deposition and novel high-resolution data on water cover and impervious urban areas to quantify the input of mercury to European rivers and lakes. This information, combined with estimates of releases from industrial installations and urban wastewater and from soils, yields an overall European budget of water mercury. Compared to previous estimates, the calculation highlights that direct deposition to permanent and temporary inland water surfaces is a dominant source of pollution. We also show that an important source is the washout of impervious urban surfaces, while releases from soil and industrial and urban wastewater play a lesser, albeit sizable role. The contribution of wastewater to mercury releases is expected to decrease over time because of more stringent regulations on mercury use. The analysis confirms that reducing atmospheric deposition (hence air releases) of mercury remains the single key action to control pollution. However, we show that control of urban runoff discharges to water bodies may be the most effective water management measure in order to reduce mercury input to coastal and in-land water bodies.